Gemcitabine-Incorporated G-Quadruplex Aptamer for Targeted Drug Delivery into Pancreas Cancer - Jun Young Park; Ye Lim Cho; Ju Ri Chae; Sung Hwan Moon; Won Gil Cho; Yun Jung Choi; Soo Jin Lee; Won Jun Kang (Elsevier, 2018)
Gemcitabine has been considered a first-line chemotherapy agent for the treatment of pancreatic cancer. However, the initial response rate of gemcitabine is low and chemoresistance occurs frequently. Aptamers can be effectively internalized into cancer cells via binding to target molecules with high affinity and specificity. In the current study, we constructed an aptamer-based gemcitabine delivery system, APTA-12, and assessed its therapeutic effects on pancreatic cancer cells in vitro and in vivo. APTA-12 was effective in vitro and in vivo in pancreatic cancer cells with high expression of nucleolin. The results of in vitro cytotoxicity assays indicated that APTA-12 inhibited the growth of pancreatic cancer cell lines. In vivo evaluation showed that APTA-12 effectively inhibited the growth of pancreatic cancer in Capan-1 tumor-bearing mice compared to mice that received gemcitabine alone or vehicle. These results suggest that the gemcitabine-incorporated APTA-12 aptamer may be a promising targeted therapeutic strategy for pancreatic cancer. Keywords: aptamer, aptamer-drug conjugates, G-quadruplex, gemcitabine, pancreatic cancer